Naming New Stimuli After Selection by Exclusion - Costa, Aline Roberta Aceituno da; Grisante, Priscila Crespilho; Domeniconi, Camila; Rose, Julio Cesar Coelho de; Souza, Deisy das Gracas de (Paidéia (Ribeirão Preto), 2013)
Responding by exclusion in matching-to-sample tasks is a robust behavioral pattern in humans. A single selection, however, does not ensure learning of the arbitrary relationship between the sample and the selected comparison stimulus. The present study aimed to investigate the amount of exposure required until eight preschoolers were able to name two undefined pictures, matched by exclusion, to two undefined words. After establishing a matching-to-sample baseline between pictures and dictated words, two new words were introduced in exclusion probes. On each probe, a new word was dictated and the matrix of comparison stimuli included a new picture and two experimentally defined pictures. Naming emerged after three to10 exclusion trials. Correct naming tended to occur more reliably when the teaching phase established stimulus control by selection.